Experimental and numerical studies on axially loaded reinforced square hollow section T-joints. (1st August 2019) - Ozyurt, E.; Das, S.
Highlights: This paper presents a study on reinforced SHS T-joints. The study was completed using nine full-scale tests and a parametric study. It was found that the behaviour of the two different reinforcing types is similar. The study found that the current design method may be unconservative. This paper presents a new design equation. Abstract: This paper presents outcomes of experimental and numerical studies completed on unreinforced, collar plate reinforced and doubler plate reinforced Square Hollow Section (SHS) T-joints subjected to axial compressive loading on the brace member. A total of nine full-scale SHS T-joint specimens were fabricated and tested, in which six specimens were reinforced with collar plate and doubler plate. Non-linear finite element (FE) models were developed using finite element code, ABAQUS. Test data was used to validate these FE models. Subsequently, validated FE models were used to conduct an extensive parametric study to investigate the effect of various geometrical parameters of main members and reinforcement plates on the ultimate capacity of reinforced SHS T-joints. The parametric study found that use of both collar and doubler plate reinforcements significantly increase the ultimate capacity of SHS T-joints. Thickness of the reinforcing plate has a positive effect if the thickness of the reinforcing plate is limited to twice the thickness of the chord member. This study, however, found that the capacity of a reinforced SHS T-joint is not dependent on the type of reinforcing plate. The study concludes that the maximum capacity that can be achieved from a reinforced joint is about double the capacity of a similar unreinforced joint. It was found that the Eurocode EN 1993-1-8 overestimates the capacity of reinforced SHS T-joints. Therefore, a new design method for predicting the ultimate capacity of the collar plate and doubler plate reinforced SHS T-joints was developed and this new design method is presented in this paper.